Progress and Challenges in the Synthesis of AlON Ceramics by Spark Plasma Sintering. Issue 1 (2nd January 2017) - Li, Xibao; Huang, Juntong; Luo, Junming
ABSTRACT: γ -aluminium oxynitride (AlON) has an excellent thermal and chemical stability, which makes AlON an attractive candidate for a wide range of applications. Production of transparent AlON is extremely challenging because residual porosity must be reduced to an absolute minimum. This can be achieved by spark plasma sintering (SPS) and introducing sintering additives. This article provides a review of research activities that concentrate on the development of spark plasma reaction sintering of AlON ceramics with and without sintering additives. Influence of the most important operating parameters (atmosphere, temperature, processing time, heating rate, etc) on product characteristics and process dynamics is reviewed for AlON ceramics. Comparison of SPS over conventional methods including pressureless sintering, hot pressing sintering and others is demonstrated. Recent advances and challenges in the synthesis of AlON ceramics by SPS are also discussed. GRAPHICAL ABSTRACT: